2022
DOI: 10.3390/ani12070901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginger Powder on Production Performance, Antioxidant Status, Hematological Parameters, Digestibility, and Plasma Cholesterol Content in Broiler Chickens

Abstract: The effect of dietary ginger powder on the production performance, digestibility, hematological parameters, antioxidant status, dietary oxidation stability, and plasma cholesterol content of broiler chickens was investigated. Ginger powder was included in the diet at 0, 5, 10, or 15 g/kg. Total antioxidant capacity and malondialdehyde in sera samples, superoxide dismutase activity, glutathione peroxidase, catalase, and malondialdehyde in liver samples, and the peroxide value and acid value of the stored diets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…This lower serum TC and TGs may suppress the fatty acid transport from the liver to adipose tissue, resulting in lower abdominal fat content as well as higher DY in the birds fed herbal rations [ 29 ], which is similar to the previous findings [ 20 , 22 ]. Birds served herbal rations showed a tendency toward higher liver percent due to lower dietary fat absorption [ 30 ], lipase activity [ 31 ], and/or hepatic lipogenesis [ 32 ] in broilers. Moreover, bioactive component-enriched herbs given to the bird revealed lower liver enzymatic activity, indicating less hepatic damage and a better percentage.…”
Section: Discussionmentioning
confidence: 99%
“…This lower serum TC and TGs may suppress the fatty acid transport from the liver to adipose tissue, resulting in lower abdominal fat content as well as higher DY in the birds fed herbal rations [ 29 ], which is similar to the previous findings [ 20 , 22 ]. Birds served herbal rations showed a tendency toward higher liver percent due to lower dietary fat absorption [ 30 ], lipase activity [ 31 ], and/or hepatic lipogenesis [ 32 ] in broilers. Moreover, bioactive component-enriched herbs given to the bird revealed lower liver enzymatic activity, indicating less hepatic damage and a better percentage.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the effective use of feed ingredients and additives is essential to enhance chicken production performance. Effective inclusions such as enzymes, probiotics, prebiotics, or unusual products enhance feed utilization (1)(2)(3)(4). After the COVID-19 crisis and dramatic changes in the feed supply, there was a trend to depend on local feed resources to formulate poultry diets to limit imports and overcome lockdown challenges that influenced the agriculture sector (2,(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Murakami et al (2000) reported that ginger has antioxidant capabilities comparable to or greater than those of vitamin E or C when used in the same quantities. Also, Al-Khalaifah et al (2022) revealed that ginger protects oxidatively stressed cells, which can occur in many pathological conditions and experimentally by many chemicals, including hydrogen peroxide (Abdul-Majeed and Abdul-Rahman, 2022).…”
Section: Introductionmentioning
confidence: 99%